2016
DOI: 10.1016/j.jpeds.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Functional Status Are Associated with Cardiac Status and Clinical Outcome in Children with Cardiomyopathy

Abstract: Objectives To measure the health-related quality of life (HRQOL) and functional status of children with cardiomyopathy and to determine whether they are correlated with sociodemographics, cardiac status, and clinical outcomes. Study design Parents of children in the Pediatric Cardiomyopathy Registry completed the Child Health Questionnaire (CHQ; age ≥5 years) and Functional Status II (Revised) (age ≤18 years) instruments. Linear and Cox regressions were used to examine hypothesized associations with HRQOL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…20 Although lower than normative data, the majority of parent-reported scores were within the normal range (−2SD to +2 SD). 20 Parents in two small studies (n = 20-26) indicated that their child's physical but not psychosocial scores were significantly (p = 0.003) below the mean for parent-reported population data. 27,30 Parent-reported subscales were also lower for physical functioning (p = 0.003), role/social-physical (p = 0.01), general health (p < .001), and self-esteem (p = 0.002).…”
Section: Patient Populations In the Identified Studiesmentioning
confidence: 71%
See 4 more Smart Citations
“…20 Although lower than normative data, the majority of parent-reported scores were within the normal range (−2SD to +2 SD). 20 Parents in two small studies (n = 20-26) indicated that their child's physical but not psychosocial scores were significantly (p = 0.003) below the mean for parent-reported population data. 27,30 Parent-reported subscales were also lower for physical functioning (p = 0.003), role/social-physical (p = 0.01), general health (p < .001), and self-esteem (p = 0.002).…”
Section: Patient Populations In the Identified Studiesmentioning
confidence: 71%
“…– 19 Of the 11 studies that used quantitative measures, none reported effect size. Two studies, Sleeper et al 20 and Czosek et al, 21 addressed the clinical relevance of their findings by indicating the proportion of patients more than two standard deviations from the norm or whose assessment results were classified as “at risk”.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations